Effect of Hyperbaric Oxygen Exposure on Bacterial Toxin Antigen and Collagen Induced Arthritis in Animal Model - Harnanik, Titut; Soeroso, J.; Suryokusumo, M.G.; Juliandhy, T. (Nepal Medical College Journal, 2019)
Anti-cyclic citrullinated peptide antibody (ACPA) is a specific autoantibody that binds with citrullineamino acid in rheumatoid arthritis (RA). Interleukin-17a (IL-17a) is one of the cytokines that play an important role in chronic inflammation during the process of autoimmune diseases. Bacterial toxin antigen and collagen induced arthritis (ACIA) is the gold standard of RA animal model. The aim of this study was to see the effect of hyperbaric oxygen (HBO) exposure on ACIA animal models. ACIA model was made by combined antigens (bacterial toxin and collagen). A total of 24 male Balb/Cmice modelled on ACIA were divided into three groups. Eight mice did not receive HBO exposure (control group, indicated as G1), eight mice (indicated as G2) received HBO exposure for 10 days while remaining eight mice (indicated as G3) for five days. G2 mice were exposed to HBO 2.4 ATA oxygen 100% for 90 minutes (30 minutes each with two intervals of five minutes breathing with normal air) for 10 consecutive days while G3 mice were exposed only for five days. The indicators of arthritis i.e. ACPA and IL-17a were measured by enzyme-linked immunosorbent assay (ELISA) technique. A significant decrease in ACPA and IL-17a levels was seen in both HBO exposed groups (G2 and G3) compared to G1 (p<0.05). There was no significant difference in levels of ACPA and IL-17a in G3 mice and G2 mice (p > 0.05). HBO reduced inflammation in ACIA by decreasing ACPA andIL-17a levels through improvement of hypoxic conditions and showed therapeutic potential for the treatment of RA.